Review of The Origin and Evolution of Social Signals in Ducks; in Particular The Function of Courtship Displays - Dewi M Prawiradilaga (Department of Forest Resources Conservation and Ecotourism - IPB University, 1989)
Recently, there has been an increase in the use of behavioural characteristics, especially courtship behaviour, in evolutionary studies. This is because such behaviour is thought to be of fixed pattern and species specific.In waterfowl, the study of the courtship behaviour was pioneered by Heinroth (191 1). His study has been elaborated by Lorenz (1941). Following this, Johnsgard (1962) and McKinney (1975) also have contributed much in this field of study. In the beginning, Heinroth and Lorenz used the evolution of courtship displays in waterfowl as indicators of taxonomic relationships. Then, Johnsgard investigated the distribution of homologous display repertoires of Anatidae and found out the relationships of all species. Since then, the study has been directed towards the search forfactors which have been responsible for the evolution af spec if^ differences, such as the difference in frequency, in the order of displays linked in sequences and in the degree ofelaboration of plumage features reinforcing signal movements. As examples, Johnsgard (1960a) studied the courtship displays in North American black duck (Anas nrbripes) and mallard (Anas platyrhynchos), McKinney (1970) observed four species of bluewinged ducks (Anas cyanopteta, A. discors, A. clypeata and A. smithi) and Prawiradilaga (1985) investigated the grey teal (Anas gibberifrons) and chestnut teal (Anas castanea).So far, not all of these specific factors have been brought up.It is the aim of this review to examine and discuss aspects of evolution of courtship displays which have been presented; in particular the origin and evolutioh of social signals in ducks, especially those referred to specifically as courtship displays.